Socialization Of The Bondowoso Election Quick Count Application - Arifin, Zainul; Abdurrahman , Ginanjar (Universitas Muhammadiyah Jember, 2024)
Regional Head Election or simply PILKADA is a routine democratic agenda in Indonesia which is held every five years to elect regional heads. It is hoped that this Pilkada can produce leaders who are in accordance with the wishes of the people and are of high quality and will advance the region. Until now, the results of the Pilkada vote counting are still not being carried out completely simultaneously in our country digitally. For this reason, the Quick Count or also known as Parallel Vote Tabulation is a useful method for monitoring and speeding up the vote counting process. Quick Count is a process of collecting information by hundreds or even thousands of volunteers through direct monitoring of voting and vote counting at all existing polling stations (TPS).